Penerapan Model Blended Learning Dengan Menggunakan Google Classroom Untuk Mendukung Pemahaman Konsep Matematika Materi Perbandingan Trigonometri - Lailatus Shajidah; Suesthi Rahayuningsih; Ulil Nurul Imanah (PT. AHLAL PUBLISHER NUSANTARA, 2025)
This research is motivated by the limited number of studies on the implementation of the Blended Learning model utilizing Google Classroom to improve understanding of mathematical concepts, particularly in the area of trigonometric ratios. This gap is important because it significantly impacts students' ability to understand concepts and apply them in problem-solving scenarios. The purpose of this study is to evaluate the use of the Blended Learning model through Google Classroom, as well as student engagement and understanding of mathematical concepts related to trigonometric ratios. This research was conducted using a quantitative descriptive approach involving 13 10th-grade vocational high school students, with a One-Shot Case Study design. Data collection was conducted by observing teacher and student activities, as well as administering a conceptual understanding test. Findings from the observations indicate that the implementation of the learning process by the teacher achieved a score of 90.63%, which is categorized as